2005
DOI: 10.1111/j.1365-2621.2005.00953.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensorial and biological evaluation of an extruded product made from corn supplemented with soybean and safflower pastes

Abstract: A puffed product was made by extruding corn flour supplemented with soybean and safflower pastes. Mixes with the following proportions of corn flour, soybean and safflower pastes: (i) 89:8:3, (ii) 83:11:6 and (iii) 80:17:3 were extruded. The corn flour, soybean and safflower pastes used had 6.6%, 45.9% and 32.9% protein content respectively. In addition, the soybean paste contained 11.78 units of inhibited trypsin/mg of sample, which means it was appropriate for human consumption. Sensory evaluation of extrude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 11 publications
1
3
0
1
Order By: Relevance
“…The U.S. consumers were more heavily concentrated on the right half of the map, particularly in the upper right, preferring samples that are crunchy, and that have curry, cumin, salty, umami, and spicy features. As these attributes were shown to be related mostly to the level of soy in the product, this is in agreement with previous studies that demonstrated that increase in soy content decreases consumer acceptance in extruded products (Adesina and others 1998; Faller and others 1999), but contrasts those that found no significant differences across products of varying soy levels (Bakar and Hin 1985; Baskaran and others 1999; Boonyasirikool and Charunuch 2000; Senthil and others 2002; Martinez‐Flores and others 2005). The preference for snacks that are crunchy and salty rather than brittle, porous, and dark has been reported previously as well (Ward and others 1995).…”
Section: Resultssupporting
confidence: 91%
“…The U.S. consumers were more heavily concentrated on the right half of the map, particularly in the upper right, preferring samples that are crunchy, and that have curry, cumin, salty, umami, and spicy features. As these attributes were shown to be related mostly to the level of soy in the product, this is in agreement with previous studies that demonstrated that increase in soy content decreases consumer acceptance in extruded products (Adesina and others 1998; Faller and others 1999), but contrasts those that found no significant differences across products of varying soy levels (Bakar and Hin 1985; Baskaran and others 1999; Boonyasirikool and Charunuch 2000; Senthil and others 2002; Martinez‐Flores and others 2005). The preference for snacks that are crunchy and salty rather than brittle, porous, and dark has been reported previously as well (Ward and others 1995).…”
Section: Resultssupporting
confidence: 91%
“…The snacks prepared with 32% replacement levels of TSF + WWF, had the lowest value 1.49, probably due to higher addition of protein and fiber provided by TSF and WWF in the snack. In general, protein and fiber act as diluents and reduce expansion due to their ability to affect water distribution in the matrix, and to the fact that their macromolecular structure and conformation affect the extensional properties of extruded meal (Aguilar‐Palazuelos, Zazueta‐Morales, Harumi, & Martínez‐Bustos, ; Martinez‐Flores et al ., ). In general, the values obtained in our study were within the range previously reported by Korkerd, Wanlpa, Puttanlek, Uttapap, and Rungsardthong () in extruded snacks enriched with 20% of a deffated soybean meal.…”
Section: Resultsmentioning
confidence: 99%
“…[4][5][6] Cereal flours are generally low in protein content, but high in sulfur containing amino acids, while legumes are rich in protein with a high proportion of lysine and only small quantity of sulfur containing amino acids. [7][8][9][10][11] Cassava (Manihot esculenta Crantz) is a root crop with starchy tubers and is cultivated and consumed in approximately 102 countries. [12] Nevertheless, the flour is low in protein, which is a disadvantage in its wide scale use in bakery and snack foods.…”
Section: Introductionmentioning
confidence: 99%